EFFECT OF SPACING ON CAMELINA SATIVA: A NEW BIOFUEL CROP IN INDIA - ANUJA KUMARI; , MOHAMMED MOHSIN; M. C. ARYA; P. K. JOSHI; Z. AHMED (The Bioscan, 2012)
Camelina sativa (L.) Crantz (Gold of Pleasure) is a proposed biofuel species introduced in India from Austria in 2009. The experiment was conducted during 2010-2012 at the Defence Institute of Bio-Energy Research, Field station- Pithoragarh, Uttarakhand to study the effect of spacing between rows (20, 25, 30 and 35cm) on the growth, yield and oil content of C. sativa cv calena. The row spacing of 30cm showed a significantly higher threshing percentage (93.60), harvest index (11.78%), seed yield (458.89 kg/ha) and oil content in seed (38.71%) on applying least significant difference test at P=0.05. The study will be beneficial to optimize the cultivation of Camelina crop for large scale production of biofuel.